(untitled) (American Journal of Islam and Society, 2025)
Mawlana Abul Kalam Azad, a multifaceted figure, was celebrated as a thinker, orator, journalist, politician, leader, and Muslim intellectual, with a deep understanding of both Islamic and contemporary knowledge. S. Irfan Habib’s Maulana Azad: A Life offers a comprehensive and fresh biographical account, exploring key moments that shaped Azad’s life and remain relevant today (p. 2). S. Irfan Habib (b. 1931) is a prominent Indian historian of ancient and medieval India and the former Abul Kalam Azad Chair at the National Institute of Educational Planning and Administration. The book challenges prevailing historical narratives, aiming to dismantle stereotypes about the past (p. 10). Structured thematically, it includes five chapters, along with an introduction and an epilogue.